Electrochemical etching method of porous electrode and water electrolysis electrode
By electrochemical etching and high-temperature fast firing treatment on the porous nickel electrode, the problem of insufficient catalytic active surface area and bubble disengagement structure of the existing porous nickel electrode is solved, and a more efficient electrolytic hydrogen production effect is achieved.
Patent Information
- Application Number
- CN202411888439.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The existing porous nickel electrodes have room for improvement in the catalytic active surface area and bubble disengagement structure, resulting in low efficiency in producing hydrogen by electrolyzing water.
The electrochemical etching method of porous electrodes is adopted to form a loaded porous nickel ferroalloy deposition layer by performing constant current electrode deposition and etching on the nickel net, and a high-temperature fast firing treatment is carried out to improve the stability of the catalyst layer.
It effectively improves the efficiency of electrolytic water, optimizes the catalytic area and bubble disengagement structure of traditional porous electrodes, and significantly improves the catalytic performance of the electrode and the efficiency of electrolyzing hydrogen production.
Smart Images

Figure CN119465259A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a water electrolysis electrode, in particular to an electrochemical etching method for a porous electrode and the water electrolysis electrode. Background Art
[0002] As the world's dependence on fossil fuels decreases and the demand for renewable energy increases, hydrogen is increasingly valued as a clean energy carrier. Alkaline water electrolysis hydrogen production technology does not produce greenhouse gas emissions, which helps reduce the impact on the environment. Water electrolysis technology can use electricity generated by renewable energy sources such as wind and solar energy to convert these unstable and difficult-to-store energy sources into hydrogen that is easy to store and transport. In particular, technological advances and innovations in electrode materials, catalysts, and electrolyzer design in recent years have helped to improve the efficiency of water electrolysis hydrogen production and reduce costs. However, the existing water electrolysis electrode structure is still relatively simple, and there is still room for improvement in efficiency. By using reasonable methods and strategies to further increase the active area of the electrode and improve the bubble escape structure, the electrolysis efficiency can be effectively improved and the overpotential of hydrogen and oxygen evolution can be reduced.
[0003] Depositing porous nickel on commercial nickel mesh is a common technology at present. This method can effectively increase the active area of the electrode, thereby improving the catalytic efficiency. This method mainly uses nickel salt and ammonium chloride as electrodeposition precursor solutions. During the electrodeposition process, nickel is continuously deposited on the surface of the nickel mesh substrate. At the same time, due to the addition of ammonium salt, hydrogen is continuously generated on the nickel mesh substrate, which eventually guides the formation of a porous nickel deposition layer, namely porous nickel, on the nickel mesh. Porous nickel already has a large active area, but from the microscopic structural observation, it is found that there is still room for optimization of the porous structure, and the active area can be further improved.
[0004] Considering that the pore structure of porous nickel is actually macroscopic, it can be observed under a low-magnification (such as 200-500 times) microscope that the pore size of porous nickel in the actual OER process does not significantly help the escape of bubbles, but actually increases the active area of the electrode to achieve the effect of improving the electrolysis efficiency. In view of this idea, it is reasonable to speculate that continuing to use other methods to further increase the active area of the electrode and optimize the bubble escape structure under microscopic conditions can achieve better water electrolysis performance.
[0005] In summary, the existing porous nickel electrodes still have room for improvement in terms of catalytic active surface area, bubble escape structure, etc. To address this problem, a new type of electrode is urgently needed to ensure the improvement of the intrinsic active area while optimizing the bubble escape structure to achieve efficient water electrolysis for hydrogen production. Summary of the invention
[0006] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide an electrochemical etching method for a porous electrode and an electrolytic water electrode, which solves the problems of insufficient catalytic area of traditional porous electrodes and poor surface bubble escape structure; it is suitable for large-scale industrial production, and has a simple preparation process, good repetitive stability and low cost.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] A first aspect of the present invention provides an electrochemical etching method for a porous electrode, comprising the following steps:
[0009] S1: In a two-electrode system, a nickel-iron metal salt containing a pore-forming agent is used as an electroplating solution, a nickel mesh is used as a working electrode, and a platinum sheet is used as a counter electrode. Constant current electrodeposition is performed in the electroplating solution to ensure that the deposition rate remains constant, thereby obtaining a nickel mesh material loaded with a porous nickel-iron alloy deposition layer;
[0010] S2: cleaning and drying the nickel mesh material loaded with the porous nickel-iron alloy deposition layer obtained in S1;
[0011] S3: Based on the nickel mesh material loaded with the porous nickel-iron alloy deposition layer treated in S2, a high-temperature furnace is used for fast firing treatment to improve the stability of the catalyst layer;
[0012] S4: In a two-electrode system, using the prepared hydrochloric acid as the etching solution, the electrode obtained in S3 as the working electrode, and the platinum sheet as the counter electrode, constant current etching is performed to ensure that the etching rate remains unchanged, thereby obtaining an etched porous electrode product.
[0013] Furthermore, the nickel mesh is a pretreated nickel mesh, and the pretreatment process includes:
[0014] The nickel mesh was ultrasonically treated in dilute hydrochloric acid to remove the oxide on the surface, then ultrasonically treated in anhydrous ethanol to remove the hydrochloric acid and organic matter on the surface, and finally ultrasonically treated in deionized water to remove other residual impurities on the surface.
[0015] Furthermore, the concentration of the dilute hydrochloric acid is 0.1-2 mol / L, and the ultrasonic treatment time is 15 min.
[0016] Further preferably, the concentration of the dilute hydrochloric acid is 1 mol / L.
[0017] Furthermore, the nickel wire diameter of the nickel mesh is 50-300 μm, and the mesh number of the nickel mesh is 40-200 meshes.
[0018] Furthermore, in S1, in the nickel-iron metal salt electroplating solution containing a pore-forming agent, the pore-forming agent is ammonium chloride, the solvent is water, the concentration of nickel chloride is 0.02-0.2 mol / L, the concentration of ferrous chloride is 0-0.1 mol / L, and the concentration of the pore-forming agent is 0.5-3 mol / L.
[0019] More preferably, the concentration of nickel chloride is 0.1 mol / L, the concentration of ferrous chloride is 0.04 mol / L, and the concentration of pore-forming agent ammonium chloride is 3 mol / L.
[0020] Furthermore, in S1, the electrodeposition time is 10 min and the current density is 0.5 A / cm 2 -2A / cm 2 , control the temperature at 20-30℃.
[0021] Further, in S2, the cleaning process is to first rinse the surface impurities with deionized water and then rinse with anhydrous ethanol;
[0022] The drying temperature is room temperature.
[0023] Further, in S3, a fast calcination treatment is performed using an ultrafast high temperature furnace to improve the stability of the catalyst layer, wherein: the fast calcination temperature is set to 800-1200° C., the heating rate is 400° C. / s, and the fast calcination is performed under an inert atmosphere;
[0024] The catalyst structure deposited on the surface of the nickel mesh material supporting the porous nickel-iron alloy deposition layer is solidified by fast sintering, while oxygen in the catalyst layer is eliminated to improve the durability and stability of the electrode;
[0025] The fast burning high temperature is maintained for 1-3 seconds and the cooling time is 3 seconds, so that it can quickly drop to room temperature.
[0026] Furthermore, in S4, the concentration of the hydrochloric acid etching solution is 0.5-2M, the electrochemical etching time is 1-10min, and the current density is 0.02-0.5A / cm 2 , the temperature is maintained at 20-30℃;
[0027] The material obtained after etching is cleaned and dried to obtain a finished porous electrode;
[0028] The cleaning process is to first rinse the surface impurities with deionized water and then rinse with anhydrous ethanol, and the drying temperature is room temperature.
[0029] The second invention of the present invention provides a water electrolysis electrode obtained by the electrochemical etching method as described above.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1) Improving water electrolysis efficiency: The porous electrode etching method provided by the present invention can effectively improve the water electrolysis efficiency, help improve energy utilization efficiency in water electrolysis-related application scenarios, achieve more efficient water electrolysis reactions, and thus play a positive role in fields such as hydrogen production.
[0032] 2) Optimizing the shortcomings of traditional porous electrodes: The present invention provides an effective optimization solution to the problems of insufficient catalytic area and poor surface bubble escape structure of traditional deposited porous electrodes. Through subsequent electrochemical etching treatment, the microstructure of the electrode surface is improved, which makes up for the shortcomings of traditional methods and significantly improves the performance of the electrode.
[0033] 3) Applicable to industrial mass production: The present invention has good characteristics suitable for industrial mass production in both the electrodeposition process and the subsequent electrochemical etching process. This means that the invention can be stably applied in an industrial production environment, meet the needs of large-scale and batch production of electrodes, and provide strong technical support for the large-scale development of related industries.
[0034] 4) The preparation process is simple, stable and low-cost: The preparation process is simple and easy to operate, does not require complex process equipment and cumbersome operation procedures, and is easy to promote and implement. At the same time, the good repetitive stability ensures that high-quality porous electrodes with similar performance can be stably produced in multiple preparation processes, and the cost is low, which can effectively reduce the economic cost of electrode production, improve production efficiency, and enhance the competitiveness of products in the market.
[0035] 5) Refine the grains and improve the surface structure: The etching method can further refine and order the deposited spherical grains, increase the surface area of the electrode, and create a rough surface structure that is conducive to the escape of bubbles. A larger surface area means more active sites for catalytic reactions, and a structure that is conducive to the escape of bubbles can reduce the adhesion and accumulation of bubbles on the electrode surface, allowing the electrode reaction to proceed smoothly and continuously, further enhancing the catalytic performance of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a low-magnification scanning electron microscope (SEM) image of the porous nickel-iron in Example 1 of the present invention;
[0037] Figure 2 This is a low-magnification (200 times) SEM image of the porous nickel-iron electrode after etching in Example 1 of the present invention;
[0038] Figure 3 This is a high-magnification (20,000 times) SEM image of the porous nickel-iron in Example 1 of the present invention;
[0039] Figure 4This is a high-magnification (20,000 times) SEM image of the porous nickel-iron electrode after etching in Example 1 of the present invention;
[0040] Figure 5 is the electrochemical active surface area curve of the porous nickel-iron and after etching in Example 1 of the present invention;
[0041] Figure 6 It is the linear sweep voltammetry curve of the oxygen evolution reaction in Example 1 of the present invention. DETAILED DESCRIPTION
[0042] On the whole, in order to solve the problems of insufficient catalytic activity and bubble escape structure of the existing alkaline water hydrogen production electrode, the present invention designs a new type of water electrolysis electrode. The electrode includes a basic porous catalyst layer electrodeposition, sintering and curing of the deposited catalyst layer, and further electrochemical etching of the porous layer, wherein the etching treatment is the main content of the present invention. At the same time, the present invention provides an etching method for a porous electrode, which effectively improves the efficiency of water electrolysis. The present invention is mainly an optimization method for traditional deposited porous electrodes, which solves the problems of insufficient catalytic area of traditional porous electrodes and poor surface bubble escape structure. On the basis of electrodeposition, the present invention further performs electrochemical etching, which is suitable for large-scale industrial production, and has a simple preparation process, good repetitive stability and low cost. In the face of different deposition conditions, the present invention sets corresponding etching parameters to achieve precise etching of porous catalyst layers with different pore sizes and different deposition layer thicknesses, so as to achieve the effect of improving the overall electrode electrolysis performance. The etching method of the present invention can further refine and order the spherical grains obtained by deposition, and obtain a larger surface area and a rough surface structure that is conducive to bubble escape. The present invention as a whole enables the electrode to have higher catalytic performance and guides the electrode preparation method to develop in the direction of etching.
[0043] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. Any features such as preparation means, materials, structures or composition ratios not clearly described in this technical solution are regarded as common technical features disclosed in the prior art.
[0044] Example 1
[0045] 1) Pretreatment of nickel mesh:
[0046] The 50-mesh nickel mesh was subjected to ultrasonic treatment in 1 mol / L dilute hydrochloric acid to remove the oxide on the surface, and then subjected to ultrasonic treatment in anhydrous ethanol to remove the hydrochloric acid and organic matter on the surface, and finally subjected to ultrasonic treatment in deionized water to remove other residual impurities on the surface, thereby obtaining a pretreated nickel mesh;
[0047] 2) Electrodeposition of porous catalyst layer:
[0048] The nickel-iron metal salt electroplating solution includes nickel chloride, ferrous chloride, ammonium chloride and deionized water;
[0049] In the nickel-iron metal salt electroplating solution, the concentration of nickel chloride is 0.1 mol / L, the concentration of ferrous chloride is 0.04 mol / L, and the concentration of pore-forming agent ammonium chloride is 3 mol / L.
[0050] In the two-electrode system, the nickel-iron metal salt electroplating solution prepared in the above steps is placed in the deposition tank, the pretreated nickel mesh is used as the working electrode, the platinum sheet is used as the counter electrode, and the current density is 0.5A / cm 2 , time is 600s, keep the temperature at 20-30℃, and obtain the nickel mesh electrode loaded with porous nickel-iron catalyst layer. The obtained composite electrode is taken out from the deposition tank, cleaned with deionized water and anhydrous ethanol, and naturally dried, named "porous nickel-iron", and used as a subsequent comparison sample.
[0051] 3) Porous electrode sintering:
[0052] After obtaining the porous catalyst layer electrode prepared in step 2), in order to improve the stability of the catalyst layer, it is necessary to perform a curing, ie, a fast burning treatment of the catalyst layer, using an ultrafast high temperature furnace for the treatment.
[0053] The fast calcination temperature was set to 1000°C and the heating rate was 400°C / s. The specific calcination temperature was determined by parameters such as the thickness of the catalyst layer.
[0054] Fast burning is carried out under nitrogen to prevent electrode oxidation;
[0055] The fast-burning high temperature is maintained for 1 second, the cooling time is 3 seconds, and it quickly drops to room temperature. At this time, it is still a "porous nickel-iron" electrode.
[0056] 4) Porous electrode etching treatment:
[0057] The porous nickel-iron electrode obtained in step 3) is further subjected to electrochemical etching treatment, the purpose of which is to further increase the surface area of the porous catalyst layer and to etch a rough structure on the catalyst grains that is conducive to the escape of bubbles.
[0058] In the two-electrode system, the prepared 1M hydrochloric acid was used as the etching solution, the porous nickel-iron electrode obtained in step (2) was used as the working electrode, and the platinum sheet was used as the counter electrode. Each electrode was immersed in the etching solution and a constant current of 0.5A / cm was applied. 2 Etching: the etching time is 400s, the temperature is guaranteed to be 20-30℃, and the surrounding environment is ventilated.
[0059] The obtained material was cleaned and dried. The cleaning process was to first rinse the surface impurities with deionized water and then rinse with anhydrous ethanol. The drying condition was room temperature drying to obtain an etched porous catalyst layer electrode, named "porous nickel iron-etched" electrode.
[0060] 5) Electrode test
[0061] A standard three-electrode system was used with mercury / mercury oxide (Hg / HgO) as the reference electrode, 2×2 cm 2 The platinum sheet is the counter electrode, 1*1cm 2 The "porous nickel iron" electrode and the "porous nickel iron-etched" electrode prepared in Example 1 were used as working electrodes. The electrochemical test was carried out on a Corrtest electrochemical workstation, the electrolyte was 1 mol / L KOH solution, the test temperature was controlled at 25°C, and the oxygen evolution reaction was carried out.
[0062] Electrochemical active surface area test: Cyclic voltammetry was performed in the non-Faraday range (corresponding to an actual voltage of about 1.0-1.1 V) using five scanning speeds of 20 mV / s, 40 mV / s, 60 mV / s, 80 mV / s, and 100 mV / s. Then, the electrode active surface area data was obtained by plotting points and fitting the slope.
[0063] Linear scanning voltammetry test: The scanning speed is 5 mV / s, and the electrode potential is 90% iR compensated and converted into the electrode potential relative to the reversible hydrogen potential (RHE). The calculation formula is shown in formula (1):
[0064] Overpotential (V) = electrode potential + 0.059 × pH + Hg / HgO electrode potential - 1.23 (1)
[0065] In the above formula (1), pH is the pH value of the electrolyte.
[0066] Figure 1 and Figure 3 The SEM image of the porous catalyst layer named "porous nickel iron" obtained after step 3) for conventional electrodeposition;
[0067] Figure 2 and Figure 4 This is the SEM image of the "porous nickel-iron-etched" electrode after etching in step 3);
[0068] Depend on Figure 1 and Figure 2 By comparison, it can be seen that after etching, the agglomerated particle structure of the electrodeposited catalyst layer has been differentiated to a certain extent, and the gap has been increased to a certain extent, which helps to increase the catalytic active area of the porous nickel electrode. Figure 3 and Figure 4 By comparison, under high-magnification SEM observation, compared with the smoother grain surface of the traditional "porous nickel-iron" ( Figure 3 ), the grains of the “porous NiFe-etched” electrode have a distinct rough surface ( Figure 4), which can significantly optimize the process of gas bubbles escaping from the particle surface and is also an important factor in improving the electrochemical active surface area, which can be Figure 5 The active surface area characterization test was verified, and the active surface area of the etched electrode (16.64mF·cm -2 ) to the original "porous nickel-iron" electrode (8.78mF·cm -2 ), which shows that etching has a significant effect on increasing the active surface area.
[0069] Figure 6 The current-voltage curve of the oxygen evolution reaction also shows that the "porous nickel-iron-etched" electrode performs better than the "porous nickel-iron" electrode. When the current is small, the "porous nickel-iron-etched" electrode can start to generate current at a lower potential, which is related to its more active sites. At the same time, its performance at high current is also better than that of the "porous nickel-iron" electrode. This is because the etched electrode has a rough bubble escape surface. When the current is large and there are many bubbles, the bubbles can be quickly separated from the surface of the catalytic layer, reducing the solution impedance and the coverage of the active sites, thereby achieving the effect of lowering the potential.
[0070] In summary, it can be seen that the "porous nickel-iron-etched" electrode of the present invention has better oxygen evolution catalytic performance.
[0071] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for electrochemical etching of a porous electrode, characterized in that: The following steps are involved: S1: In a two-electrode system, a nickel-iron metal salt containing a pore-forming agent is used as an electroplating solution, a nickel mesh is used as a working electrode, and a platinum sheet is used as a counter electrode. Constant current electrodeposition is performed in the electroplating solution to ensure that the deposition rate remains constant, thereby obtaining a nickel mesh material loaded with a porous nickel-iron alloy deposition layer; S2: cleaning and drying the nickel mesh material loaded with the porous nickel-iron alloy deposition layer obtained in S1; S3: Based on the nickel mesh material loaded with the porous nickel-iron alloy deposition layer treated in S2, a high-temperature furnace is used for fast firing treatment to improve the stability of the catalyst layer; S4: In a two-electrode system, using the prepared hydrochloric acid as the etching solution, the electrode obtained in S3 as the working electrode, and the platinum sheet as the counter electrode, constant current etching is performed to ensure that the etching rate remains unchanged, thereby obtaining an etched porous electrode product.
2. The electrochemical etching method of a porous electrode according to claim 1, characterized in that: In S1, the nickel mesh is a pretreated nickel mesh, and the pretreatment process includes: The nickel mesh was ultrasonically treated in dilute hydrochloric acid to remove the oxide on the surface, then ultrasonically treated in anhydrous ethanol to remove the hydrochloric acid and organic matter on the surface, and finally ultrasonically treated in deionized water to remove other residual impurities on the surface.
3. The electrochemical etching method of a porous electrode according to claim 2, characterized in that: The concentration of the dilute hydrochloric acid is 0.1-2 mol / L, and the ultrasonic treatment time is 15 min.
4. The electrochemical etching method of a porous electrode according to claim 2, characterized in that: The nickel wire diameter of the nickel mesh is 50-300 μm, and the mesh number of the nickel mesh is 40-200 meshes.
5. The electrochemical etching method of a porous electrode according to claim 1, characterized in that: In S1, in the nickel-iron metal salt electroplating solution containing a pore-forming agent, the pore-forming agent is ammonium chloride, the solvent is water, the concentration of nickel chloride is 0.02-0.2 mol / L, the concentration of ferrous chloride is 0-0.1 mol / L, and the concentration of the pore-forming agent is 0.5-3 mol / L.
6. The electrochemical etching method of a porous electrode according to claim 1, characterized in that: In S1, the electrodeposition time is 10 min and the current density is 0.5 A / cm 2 -2A / cm 2 , control the temperature at 20-30℃.
7. The electrochemical etching method of a porous electrode according to claim 1, characterized in that: In S2, the cleaning process is to first rinse the surface impurities with deionized water and then rinse with anhydrous ethanol; The drying temperature is room temperature.
8. The electrochemical etching method of a porous electrode according to claim 1, characterized in that: In S3, an ultrafast high temperature furnace is used to perform a fast calcination treatment to improve the stability of the catalyst layer, wherein: the fast calcination temperature is set to 800-1200° C., the heating rate is 400° C. / s, and the fast calcination is performed under an inert atmosphere; The catalyst structure deposited on the surface of the nickel mesh material supporting the porous nickel-iron alloy deposition layer is solidified by fast sintering, while oxygen in the catalyst layer is eliminated to improve the durability and stability of the electrode; The fast burning high temperature is maintained for 1-3 seconds and the cooling time is 3 seconds, so that it can quickly drop to room temperature.
9. The electrochemical etching method of a porous electrode according to claim 1, characterized in that: In S4, the concentration of the hydrochloric acid etching solution is 0.5-2M, the electrochemical etching time is 1-10min, and the current density is 0.02-0.5A / cm 2 , the temperature is maintained at 20-30℃; The material obtained after etching is cleaned and dried to obtain a finished porous electrode; The cleaning process is to first rinse the surface impurities with deionized water and then rinse with anhydrous ethanol, and the drying temperature is room temperature.
10. A water electrolysis electrode obtained by the electrochemical etching method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Nickel-based composite electrode for alkaline electrolytic cell and preparation method of nickel-based composite electrode
CN115094460A
Electrode with substrate and catalyst layer integrated composite structure and preparation method thereof
CN115369418A
Self-supporting alkaline electrolytic water hydrogen production electrode with gradient pore structure as well as preparation method and application of self-supporting alkaline electrolytic water hydrogen production electrode
CN116334679A
Alkaline electrolyzed water oxygen evolution electrode and preparation method and application thereof
CN116445964A
Nickel-based alloy composite electrode having gradient component structure, and preparation method therefor and use thereof
WO2024021403A1